2005
DOI: 10.1149/1.1834913
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Manganese Oxide/CNTs Composites as Electrode Materials for Electrochemical Capacitors

Abstract: Nanocrystalline metal oxides can be prepared with large surface area, electrochemical stability, and pseudocapacitive behavior, being able to be used as supercapacitor electrodes. Among the various metal oxides studied, amorphous and hydrated manganese oxide (a-MnO 2 •nH 2 O) is the most promising for supercapacitor electrodes due to the low cost of the raw material. In the present work, amorphous manganese dioxide (a-MnO 2 •nH 2 O) is prepared by chemical co-precipitation of Mn͑VII͒ and Mn͑II͒ in water medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
238
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(248 citation statements)
references
References 44 publications
(102 reference statements)
1
238
2
1
Order By: Relevance
“…30,39,[42][43][44][45][46] It is worth noting that such an approach is straightforward when using solution processing techniques. 6,47 Numerous researchers have shown that this strategy can result in increased capacitance by facilitating transport of charge from redox sites to the external circuit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…30,39,[42][43][44][45][46] It is worth noting that such an approach is straightforward when using solution processing techniques. 6,47 Numerous researchers have shown that this strategy can result in increased capacitance by facilitating transport of charge from redox sites to the external circuit.…”
mentioning
confidence: 99%
“…6,47 Numerous researchers have shown that this strategy can result in increased capacitance by facilitating transport of charge from redox sites to the external circuit. 33,39,42,48,49 However, there are a number of problems with this approach. Most important is that any addition of nano-conductor reduces the fraction of capacitive material present.…”
mentioning
confidence: 99%
“…Moreover, the carbon materials have good power density, good stability and low resistance for supercapacitors. Carbon materials involved activated carbon [14,15], carbon fiber [16,17], carbon nanotubes [18], and porous carbon [19,20], et al…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the carbon materials have good power density, good stability and low resistance for supercapacitors. Carbon materials involved activated carbon [14,15], carbon fiber [16,17], carbon nanotubes [18], and porous carbon [19,20], et alIn this paper, an interconnected hierarchical porous carbon (IHPC) was prepared by the polyHIPE and carbonation method based on phenolic-formaldehyde resin for supercapacitors. Structural and morphological characterizations of IHPC were carried out using field emission scanning electron microscopy (SEM), Capacitive behavior of IHPC was investigated by cyclic voltammetry and galvanostatic charge-discharge in 2 M KOH aqueous solution.…”
mentioning
confidence: 99%
“…If the scaffold is made from a carbonaceous material or any other active electrode material, it can provide a capacitance in addition to the capacitance of the deposited oxide. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] The preparation of MnO 2 · xH 2 O by a chemical route, usually from KMnO 4 , involves reduction "in situ" of Mn 7+ to Mn 4+ which can be favored by the presence of carbon. The preparation by an electrochemical route has been tried from several Mn precursors, e.g.…”
mentioning
confidence: 99%